Social Aspects of Dementia Prevention from a Worldwide to National Perspective: A Review on the International Situation and the Example of Italy - Giovanna Ricci (Behavioural Neurology)
At the moment, dementia is affecting around 47 million people worldwide, with a forecast amount of 135 million affected people in 2050. Dementia is a growing health concern worldwide with no treatment currently available, but only symptomatic medication. Effective interventions in the prevention and management of dementia are urgently needed to contain direct and indirect costs of this disease. Indeed, the economic impact of dementia is a vast and continually growing figure, but it is still difficult to quantify. Due to an increase in both the disease spreading and its direct and indirect costs, national and international action plans have to be implemented. As a virtuous example, the Italian national plan for dementia has been summarized. Faced with an increasingly less sustainable disease impact at national and international levels, the plan suggests that it is certainly the entire welfare model that should be rethought, strengthening the network of services and providing interventions to support affected people and their caregivers. Alongside this synergistic approach, scientific research could play a crucial role for pharmacological and nonpharmacological treatments capable of delaying the state of loss of self-sufficiency of the patient, with a significant impact on social and health costs.